Pediatric glioblastoma multiforme: A single-institution experience - Mansour Ansari; Hamid Nasrolahi; Amir-Abbas Kani; Mohammad Mohammadianpanah; Niloofar Ahmadloo; Shapour Omidvari; Ahmad Mosalaei (Indian Journal of Medical and Paediatric Oncology)
Background: Glioblastoma multiforme (GBM) is the most common astrocytoma in adults and has a poor prognosis, with a median survival of about 12 months. But, it is rare in children. We report our experience on the pediatric population (20 years or younger) with GBM. Patients and Methods: Twenty-three patients with GBM who were treated at our hospital during 1990-2008 were evaluated. Results: The mean age was 15.2 years, and the majority of them (14/23) were male. All had received radiotherapy and some had also received chemotherapy. The mean survival was 16.0 months. Two cases survived more than 5 years. Age, radiation dose and performance status were significantly related to survival. Conclusion: GBM in pediatric patients were not very common in our center, and prognosis was unfavorable.